Total synthesis of pachastrissamine (jaspine B) enantiomers from D-glucose - Ramana, C. V.; Giri, Awadut G.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Tetrahedron Letters, 2007)
Synthesis of both enantiomers of pachastrissamine is described from a common chiral template. The stereoselective construction of the central tetrahydrofuran units was based on the pseudodesymmetrization of a pentodialdo-1,4-furanose derivative taking advantage of the latent symmetry present. (c) 2006 Published by Elsevier Ltd.
Keywords: 4-furanose; chiron approach; Ohira-Bestmann reaction; pachastrissamine/jaspine B; pentodialdo-1; ring isomerization

[2+2+2]-cyclotrimerization approach for the synthesis of enantiopure isochromans using a carbohydrate derived dialkyne template - Ramana, C. V.; Suryawanshi, Sharad B. (Tetrahedron Letters, 2008)
An easy access to enantiopure isochromans through cross alkyne trimerization of a glucose derived dialkyne was developed. One of the synthesized isochromans was converted into a novel tricyclic nucleoside by simple transformations. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: isochroman; tricyclic nucleoside; Vorbruggen reaction; Wilkinson's catalyst; [2+2+2]-Cyclotrimerization

Pd(II)-mediated alkynediol spiroketalization: first total synthesis of (-)-cephalosporolide E and (+)-cephalosporolide F - Ramana, C. V.; Suryawanshi, Sharad B.; Gonnade, Rajesh G. (Journal of Organic Chemistry, 2009)
Herein we describe a concise assembly of the central 1.6-dioxaspiro[4.4]nonane core of cephalosporolides E/F by employing a Pd-mediated alkynediol cycloisomerization and their total synthesis. On the basis of spectroscopic data and optical rotation values, the absolute configurations of cephalosporolides E/F were proposed.

Cytotoxic activity of 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda against human cancer cells - Shriram, Varsha; Kumar, Vinay; Kishor, P. B. Kavi; Suryawanshi, Sharad B.; Upadhyay, Ankur K.; Bhat, Manoj K. (Journal of Ethnopharmacology, 2010)
Ethnopharmacological relevance: Eulophia nuda L. (Orchidaceae) is a medicinally important terrestrial orchid used for the treatment of tumours and various health problems by the local healers throughout the Western Ghats region in Maharashtra (India). Aim of the study: To isolate the active molecule from Eulophia nuda and to study its cytotoxic potential against human cancer cells. Materials and methods: The crude methanolic extract of Eulophia nuda tubers was fractionated by stepwise gradient of the solvents chloroform-methanol to isolate the pure compound. Isolated pure compound was assessed for its cytotoxic potential against human breast cancer cell lines, MCF-7 and MDA-MB-231 using MTT assay. Structure elucidation of the isolated active compound was carried out by extensive spectroscopic analysis including (1)H NMR, (13)C NMR, NOESY, COSY, LC-MS and IR. Results: The isolated active molecule was identified as phenanthrene derivative 9,10-dihydro-2,5-dimethoxyphenanthrene-1,7-diol. This compound showed good antiproliferative activity against human breast cancer cell lines MCF-7 (91%) and MDA-MB-231 (85%) at 1000 mu g/ml concentration. Conclusion: 9,10-Dihydro-2,5-dimethoxyphenanthrene-1,7-diol from Eulophia nuda tubers showed good growth suppressive effect against human cancer cell lines MCF-7 and MDA-MB-231 making it a potential biomolecule against human cancer. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cytotoxic activity; Eulophia nuda; Phenanthrene derivatives

Isochroman- and 1,3-dihydroisobenzofuran-annulation on carbohydrate templates via [2+2+2]-cyclotrimerization and synthesis of some tricyclic nucleosides - Suryawanshi, Sharad B.; Dushing, Mangesh P.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2010)
The synthesis of enantiopure tricyclic systems comprising isochroman or dihydroisobenzofuran units integrated with sugar templates has been documented. The alkyne cylotrimerization reaction has been employed with easily accessible sugar diynes for the key bicyclic ring construction and thus a provision to alter the functional groups on the newly formed aromatic rings. By selecting two representative trimerization products, we have synthesized the tricyclic nucleosides by simple synthetic manipulations. (c) 2010 Elsevier Ltd. All rights reserved.
Keywords: Dihydroisobenzofuran; Dihydroisobenzopyran; Modified nucleosides; Vorbruggen reaction; [2+2+2] cyclotrimerization